Comparative Analysis of Agricultural Financing in Some Countries - Inten Meutia; Mohamad Adam; Titin Vegirawati (Institute for Research and Community Empowerment (LPPM TAZKIA), 2017)
Abstract. This study aims to find the similarities and differences in financing practices that occurred in The Agricultural Bank of Iran, China, Sudan, Malaysia and Baitul Maal wat Tamwil in Indonesia, and to obtain best farmers and agricultural enterpreneurs financing practices. This study used qualitative approach. Case study is selected as strategy in this research. The method of data collecting is documentation. Data is obtained from websites and annual reports of each agricultural bank. The data collected is the bank's policy data on financing distributed to farmers and agricultural enterpreneurs. Agricultural Bank of China uses interest based product. This bank offer flexible loan and flexible time of payment. Agricultural bank in Iran and Sudan offer partnership and constant profit financing products to farmers. Malaysia and BMT Sidogiri in Indonesia offer constant profit contract. But their financing contract, tawarruq and Bay al Wafa are still controversial contracts. Observed agricultural banks have been using sharia priciples, except for Agricultural Bank of China. The financing product that has been used since the time of the Prophet has been applied by the agricultural banks. However, there are still controversial financing used by these banks.